2015
DOI: 10.1007/978-3-319-16366-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction from Weight Management and Physical Activity Interventions

Abstract: Obesity and low levels of physical activity are associated with a higher risk of breast cancer recurrence and mortality. Currently, over 65% of breast cancer survivors are overweight or obese, and fewer than 30% engage in recommended levels of physical activity. The reason for low adherence to lifestyle guidelines is likely multifactorial. Given the continuing trend of increased obesity and physical inactivity in the United States, worldwide and in breast cancer survivors, more research showing the direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Studies in breast cancer have shown that weight loss reduces markers of recurrence, including total and free estradiol, insulin, adiponectin and inflammatory and cancer-promoting proteins. 62,63 Few studies have investigated the benefits of weight loss following treatment for endometrial cancer and all have had limited follow up, been underpowered to examine the effect of the intervention on survival and used diet and exercise regimes that failed to achieve substantial weight loss. 64 Only one RCT reported survival at 24 months and found no improvement in overall survival with a lifestyle and behavioural intervention.…”
Section: Long-term Outcomes In Obese Patients With Endometrial Cancermentioning
confidence: 99%
“…Studies in breast cancer have shown that weight loss reduces markers of recurrence, including total and free estradiol, insulin, adiponectin and inflammatory and cancer-promoting proteins. 62,63 Few studies have investigated the benefits of weight loss following treatment for endometrial cancer and all have had limited follow up, been underpowered to examine the effect of the intervention on survival and used diet and exercise regimes that failed to achieve substantial weight loss. 64 Only one RCT reported survival at 24 months and found no improvement in overall survival with a lifestyle and behavioural intervention.…”
Section: Long-term Outcomes In Obese Patients With Endometrial Cancermentioning
confidence: 99%
“…Maintaining a healthy weight [ 18 , 19 ], performing physical activity [ 19 , 20 , 21 ], reducing dietary fat consumption [ 13 ], consuming fruits and vegetables [ 19 ], and limiting alcoholic intake [ 14 ] are important lifestyle behaviors that may reduce BC recurrence. Although BC survivors may be aware of the relationship between lifestyle and risk of BC recurrence [ 22 , 23 ], many report poor adherence to cancer prevention strategies aimed at reducing recurrence [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average reported weight gain is 2.5-5 kg, 5 but a gain of 10 kg or more is not uncommon. 14 The reasons for weight gain are multifactorial and include "stress eating," reduced activity because of fatigue or other treatment-related adverse effects, lowered metabolic rate from chemotherapy, and use of pre-and post-chemotherapy medications such as dexamethasone. 14 Weight gain is most common in women who experience treatment-related menopause and is often accompanied by relative fat gain and muscle loss.…”
Section: How Does Body Weight Influence the Prognosis For Breast Cancer?mentioning
confidence: 99%
“…14 The reasons for weight gain are multifactorial and include "stress eating," reduced activity because of fatigue or other treatment-related adverse effects, lowered metabolic rate from chemotherapy, and use of pre-and post-chemotherapy medications such as dexamethasone. 14 Weight gain is most common in women who experience treatment-related menopause and is often accompanied by relative fat gain and muscle loss. 15 Several observational studies have shown that gaining weight during or after breast cancer treatment increases the risk of recurrence and reduces survival, irrespective of baseline body mass index (BMI).…”
Section: How Does Body Weight Influence the Prognosis For Breast Cancer?mentioning
confidence: 99%